Stopper fragments in parenteral preparations: a potential problem - Gomes Pucciarelli, Janayna; Watanabe, Evandro; de Godoy, Simone; Maciel Monteiro, Rachel; Castania Amadio Domingues, Pedro; Marchi-Alves, Leila Maria (Revista Prevenção de Infecção e Saúde, 2022)
Introduction: The presence of extrinsic particles in injectable solutions is a medication error of usual occurrence that may has important clinical significance. This study aimed to evaluate the presence of stopper fragments in solution derived from bottle-vial after the preparation of drugs using different sorts of needles. Outline: Experimental study, wherein 50 bottles-vials were used, divided into groups. Group 1: stopper perforated with three-bevel tip needle; Group 2: stopper perforated with blunt tip needle; Group 3: without perforation of the stopper. The figure and the size of the particles were determined through optic microscopy. The data were analyzed by means of descriptive statistics and the differences among the groups were analyzed through Fischer’s Exact Test. Results: It was verified the presence of six stopper fragments in the solution derived from five bottles which had the stoppers perforated by three-bevel tip needle (29.4%) and the two fragments in two bottles which had the stoppers perforated with blunt tip needle (11.8%), with significant difference (p=0.044) in the comparison among the groups. The three-bevel tip needle produces larger particles (0.36 mm2) than then blunt tip needle (0.12mm²). Implications: Risk evaluations must enable the limitation, the detection, and the rejection of atypical unities at the time of the drugs’ preparations, preserving patient safety.